PENGARUH TINGKAT SUKU BUNGA, NILAI TUKAR, DAN INFLASI TERHADAP HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGES TAHUN 2021-2023 - Kartini; Kara, Muslimin (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study aims to determine the influence of interest rates, exchange rates, and inflation on the stock prices of companies in the food and beverages sub-sector. The method used in this study is a quantitative method. This study uses secondary data with the sampling technique used, namely purposive sampling. The research sample was 180 data obtained from 15 food and beverages companies that passed the sampling process, using quarterly data. The data in this study was processed with the help of the IBM SPSS for windows program. The results of this study show that partially interest rates have a significant effect on stock prices. Exchange rates and inflation partially do not have a significant effect on stock prices. However, simultaneously the variables of interest rates, exchange rates, and inflation have a significant effect on the stock price of food and beverages companies.